2012
DOI: 10.29309/tpmj/2012.19.05.2325
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Methodologies;

Abstract: Objective: To determine preferences of medical students for modes of teaching, qualities of a good teacher and assessmenttechniques in medical education. Design: A descriptive cross-sectional study. Setting: Lahore Medical and Dental College, Lahore. Period:January 2011. Material & Methods: All students of third and fourth year MBBS classes were included in the study (n=127). A pre-testedquestionnaire was used for data collection. A 7-point Likert scale ranging from 1(strongly disagree) to 7(strongly agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…A very small percentage of students in our study preferred SPs (2%), OWLs (1%), and GSs (1%). This finding was consistent with a study done by Mukhtar et al 13 who also found that the least preferred methodology was the OWL.…”
Section: Discussionsupporting
confidence: 92%
“…A very small percentage of students in our study preferred SPs (2%), OWLs (1%), and GSs (1%). This finding was consistent with a study done by Mukhtar et al 13 who also found that the least preferred methodology was the OWL.…”
Section: Discussionsupporting
confidence: 92%
“…The least favored styles were those that involved didactic or one-way teaching such as students' presentations, intradepartmental lecture (IDL) or guest lecture. Same results were observed by Bhalli et al and Mukhtar et al [7,24].…”
Section: Discussionsupporting
confidence: 88%